Rural settlements and agrarian reform in Brazil: organization of agricultural production, living conditions and sustainability - Ferreira, Ângela Duarte D.; Silva, Cláudia Pereira da; Antuniassi, Maria Helena Rocha (Cadernos CERU, 1999)
This paper looks at the reconstruction of family farming in settlements estabilished through Agrarian Reform in Brazil. We begin with a general discussion of the situation reigning in the country and then take a more specific look at the settlements located in the state of Paraná, in southern Brazil. We present data on the basic characteristics of the settlements and show how the latter are structured around the organization of agricultural production of the sustainability ofthese settlements and the role they play in the construction of patterns of rural and agricultural development in Brazil.